Research Review: Neuropsychological test performance in pediatric obsessive–compulsive disorder – a meta‐analysis. (13th April 2015) - Abramovitch, Amitai; Abramowitz, Jonathan S.; Mittelman, Andrew; Stark, Abigail; Ramsey, Kesley; Geller, Daniel A.
<x xml:space="preserve">Abstract</x> Background Research into the neuropsychology of pediatric obsessive–compulsive disorder (OCD) reveals inconsistent results, limiting the ability to draw conclusions about possible neurocognitive deficits in youth with OCD. The aim of this study was to conduct a meta‐analysis of the available literature. Methods We identified 36 studies, of which 11 studies met inclusion criteria. Results were categorized into nine functional subdomains: planning, response inhibition/interference control, set shifting/cognitive flexibility, verbal memory, nonverbal memory, processing speed, working memory, visuospatial functions, and attention. For each domain, weighted pooled Hedges' g effect size was calculated using random model analyses. Results Small effect sizes were found across all subdomains, none of which were found to be statistically significant. Discussion Results indicate that youth with OCD do not exhibit noteworthy neuropsychological deficits. This is in line with recent suggestions that OCD may not be characterized by clinically meaningful neuropsychological impairments. However, the small number of available controlled studies highlights the urgent need for more neuropsychological research in this population, as well as for further exploration of the neurodevelopmental hypothesis in pediatric OCD. Finally, the relatively low persistence rates of OCD into adulthood should be taken under consideration, especially in the context of the putative neuropsychological performance differences between adult and pediatric OCD populations.